The infinity of lists - Eco, Umberto (New York : Rizzoli, 2009)
Reflections on how the idea of catalogs has changed over the centuries and how, from one period to another, it has expressed the spirit of the times. Companion to the author's History of beauty and On ugliness.
The shield and its form -- The list and the catalogue -- The visual list -- The ineffable -- Lists of things -- Lists of places -- There are lists and lists -- Exchanges between list and form -- The rhetoric of enumeration -- Lists of mirabilia -- Collections and treasures -- The Wunderkammer -- Definition by list of properties versus definition by essence -- The Aristotelian telescope -- Excess, from Rabelais onwards -- Coherent excess -- Chaotic enumeration -- Mass-media lists -- Lists of vertigos -- Exchanges between practical and poetic lists -- A non-normal list.
"Published in conjunction with the exhibition The infinity of lists, presented by the Musee du Louvre, Paris, in November 2009 and organized by Umberto Eco"
Bibliografija: str. 406-407. Kazalo.
Keywords: Katalozi